Functional parathyroid cystic adenoma: A rare cause of hypercalcemic crisis with primary hyperparathyroidism - B S Sumana; M Sabaretnam; Vijaya Sarathi; Akshatha Savith (Wolters Kluwer Medknow Publications, 2015)
We discuss a case of primary hyperparathyroidism caused by a giant cystic parathyroid adenoma presenting with neck swelling and hypercalcemic crisis. Fine-needle aspiration cytology of presumed thyroid swelling from one of the two sites aspirated yielded clear fluid but was not attributed to parathyroid pathology. Elevated serum calcium and intact parathormone (iPTH) levels suggested preoperative parathyroid pathology. Ultrasound neck and sestamibi scan for parathyroid localization were not conclusive. Due to resistant hypercalcemia, the patient underwent emergency bilateral neck exploration and excision of the identified left superior parathyroid cyst along with total thyroidectomy. Monitoring of intra-operative iPTH helped complete removal of hyperfunctioning parathyroid tissue. Histopathological examination confirmed the parathyroid cyst. Cystic parathyroid adenoma should be considered in the differential diagnosis of cystic neck lesions.